FTIR and rheology study of alginate samples: Effect of radiation - Mollah, M.Z.I.; Faruque, M. R. I.; Bradley, D.A. *; Khandaker, Mayeen Uddin *; Assaf, Saphwan Al (Elsevier, 2023)
Two well characterised alginate samples with high and low M/G ratio were subjected to radiation decontamination dose at 15 kGy. Subsequently, a number of techniques were used to determine the effect of radiation on the gelling properties. These techniques include: (GPC-MALLS) gel permeation chromatography linked to a multi-angle laser light scattering and refractive index detector for the determination of molecular weight and distribution. To observe the mechanics, the deformation with flow of α-β alginates rheological measurements in the dynamic oscillation modes, and distinguish the functional group of the samples along with identifying the M/G ratio for quantitative determination of mannuronic and guluronic acid, the FTIR techniques were performed respectively. The results showed clear reduction in the molecular weight following irradiation which was also accompanied by a loss of the gelling properties as well as clear reduction intensity of FTIR peak at 1080-1400 cm